ANALYSIS OF THE IMPLEMENTATION OF WATCH DUTIES FOR SHIP CREW ON THE KMP SURYA 777 - I Made Bayu Oka Pramana; Bustamin; Diah Vitaloka Hartati (STKIP Subang, 2026)
This study aims to identify and evaluate the arrangement and implementation of rest hours management in carrying out watch duty on KMP. Surya 777. Watch duty is a duty or obligation carried out by watch officers in rotation to maintain and ensure the security, smoothness and safety of ship operations. This study uses a qualitative approach through interviews, observations and analysis of related documents. Research informants consist of Chief Officer, helmsman, and sailors who are directly involved in the implementation of watch duty. and literature study. The results of the study indicate that the implementation of watch duty and rest hours on KMP. Surya 777 has followed STCW and MLC standards. However, there are several obstacles or challenges found in its implementation, namely overtime, lack of understanding of the crew regarding the importance of watch duty and rest time management. With this study, it is hoped that the implementation of watch duty and rest time management will improve sailing safety and crew performance optimally.